Perspectives: Advertising and climate change – Part of the problem or part of the solution?. Issue 2 (17th February 2023) - Hartmann, Patrick; Marcos, Aitor; Castro, Juana; Apaolaza, Vanessa
Abstract: The advertising industry has a direct carbon footprint but also contributes to climate change by stimulating unsustainable economic growth, promoting climate-harmful consumerism, and greenwashing polluting products and companies. However, advertising can also play a pivotal role in fighting climate change. The advertising industry can reduce its carbon footprint, fight greenwashing, and cut ties with polluting clients and industries. Green advertising can shift consumers away from climate-harmful consumption patterns toward a low-carbon culture by providing accurate information and leveraging psychological processes such as moral satisfaction, nature experiences, and fear responses, among others. For advertising research to play a significant role in this paradigm shift, it should focus more specifically on climate-relevant behaviours instead of on general green consumer behaviour, and adopt a more holistic approach to analyze the role of advertising not only in influencing individual consumers' decisions but also in sustaining a cultural narrative that promotes climate protection.